PROSES PEMBELAJARAN IPA DI SMPN 1 BABIRIK KABUPATEN HULU SUNGAI UTARA - Mauliani; Arif Sholahuddin; Maya Istyadji (Bajang Institute, 2024)
This study aims to describe the science learning process in terms of process standards and to describe the competence of science teachers in terms of education staff standards. This research uses descriptive research with a qualitative approach. Data collection techniques using observation techniques, interviews, and documentation. The validation technique uses data triangulation. The data analysis technique in this study is by means of data reduction, data presentation, and data verification. The results showed that in general the science learning process at SMPN 1 Babirik was in accordance with the standard process. The lesson plans prepared by science teachers meet most of the indicators in Permendikbud No. 22 of 2016 concerning RPP components. In general, the planning, implementation, and evaluation stages are in accordance with process standards. The competence of science teachers at SMPN 1 Babirik has also met the standards of teaching staff